ANTI-MICROBIAL ACTIVITY OF GINGER FLOWER AGAINST SOME CAUSATIVE AGENT OF ACUTE RESPIRATORY INFECTION - Zai, Arni Marlinda; Suandy, Suandy; Tobing, Andrico Napolin Lumban (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2021)
Various microorganisms such as Streptococcus pneumonia, Haemophilus influenza, Chlamydia spp, and Mycoplasma pneumonia can cause ARI. The ginger flower which contains various phytochemicals that have potential anti-microbial. Recent study was aimed to explore the anti-microbial properties of ginger flower extract. This study was experimental in vitro study with the disc diffusion method. The ethanol extract of Ginger flowers was obtained by maceration method with a ratio of Simplicia to solvent 1:10. Then it concentrated with a rotary evaporator. The ethanol extract of the ginger flower was diluted by DMSO into four concentrations viz. 100%, 75%, 50%, and 25%. The anti-microbial activity assay used three different types of microbes (Streptococcus pneumonia, Haemophilus influenza, and Candida albicans) different in 3 repetitions. There were significant differences each concentration on the width of clear zone among Streptococcus pneumonia (P-value = 0.010), Haemophilus influenza (P-value = 0.011), and Candida albicans (P-value = 0.005). Also, all concentrations of ginger flower extract showed no significant difference between positive controls; however, significant differences were found for negative controls. Hence, It can be concluded that 25% of ginger flower extract has been sufficient to inhibit the growth of various tested microorganisms.